MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENERAPKAN STRATEGI PEMBELAJARAN KOOPERATIF MODEL CATUR ASRAMA PADA SISWA KELAS VI SD NEGERI 1 ASTINA SINGARAJA - Sukadi Sukadi (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
This study was aimed at improving students achievement in social studies and civiceducation classes through implementing Hindus Cooperative learning strategy (a model of CaturAsrama) for students grade VI of SD Negeri 1 Astina, Singaraja. To achieve this objective thisstudy was conducted by using classroom action research. There were two teachers who practicedthis strategy, those were social studies and civic education teacher. The result of this studyrevealed that the use of Catur Asrama as a cooperative learning strategy could improve studentsachievement (concept attainment, attitude, and presentation skills) in social studies andcivic education classes for students grade VI of SD Negeri 1 Astina Singaraja. The implicationof this study need elementary school teachers continually to develop and study about the possibilityof using Catur Asrama as a cooperative learning strategy in order to enhance elementaryschool students achievement.Keywords: Student, Cooperative Learning, Catur Asrama